Nonlinear Dynamic Analysis of a Full-Scale Unreinforced Adobe Model - Tarque, Nicola (2014)
This paper describes the results of a numerical study of a full-scale adobe building model tested on a shaking table. Material properties of adobe masonry were calibrated to represent the wall in-plane seismic behavior, based on a prior numerical analysis of an adobe wall carried out by the authors. The inelastic part of the constitutive model was represented by a softening curve in tension and by a hardening/softening behavior in compression; thus, the fracture energy is a key issue in the modeling process. A finite element model that relies on a homogenous continuum approach was developed in Abaqus/Explicit software. The damage evolution in the numerical simulation represented fairly well the experimental crack pattern, for in-plane and out-of-plane seismic effects. Overall, the calibrated material properties and the explicit solution scheme proved to be appropriate for simulating the seismic behavior and predicting capacity of unreinforced adobe structures subjected to seismic loading.